A systematic review and meta-analysis of traumatic intracranial hemorrhage in patients taking prehospital antiplatelet therapy: Is there a role for platelet transfusions?. Issue 6 (June 2020) - Alvikas, Jurgis; Myers, Sara P.; Wessel, Charles B.; Okonkwo, David O.; Joseph, Bellal; Pelaez, Carlos; Doberstein, Cody; Guillotte, Andrew R.; Rosengart, Matthew R.; Neal, Matthew D.
Abstract : BACKGROUND: Platelet transfusion has been utilized to reverse platelet dysfunction in patients on preinjury antiplatelets who have sustained a traumatic intracranial hemorrhage (tICH); however, there is little evidence to substantiate this practice. The objective of this study was to perform a systematic review on the impact of platelet transfusion on survival, hemorrhage progression and need for neurosurgical intervention in patients with tICH on prehospital antiplatelet medication. METHODS: Controlled, observational and randomized, prospective and retrospective studies describing tICH, preinjury antiplatelet use, and platelet transfusion reported in PubMed, Embase, Cochrane Reviews, Cochrane Trials and Cochrane DARE databases between January 1987 and March 2019 were included. Investigations of concomitant anticoagulant use were excluded. Risk of bias was assessed using the Newcastle-Ottawa scale. We calculated pooled estimates of relative effect of platelet transfusion on the risk of death, hemorrhage progression and need for neurosurgical intervention using the methods of Dersimonian-Laird random-effects meta-analysis. Sensitivity analysis established whether study size contributed to heterogeneity. Subgroup analyses determined whether antiplatelet type, additional blood products/reversal agents, or platelet function assays impacted effect size using meta-regression. RESULTS: Twelve of 18, 609 screened references were applicable to our questions and were qualitatively and quantitatively analyzed. We found no association between platelet transfusion and the risk of death in patients with tICH taking prehospital antiplatelets (odds ratio [OR], 1.29; 95% confidence interval [CI], 0.76–2.18; p = 0.346; I 2 = 32.5%). There was no significant reduction in hemorrhage progression (OR, 0.88; 95% CI, 0.34–2.28; p = 0.788; I 2 = 78.1%). There was no significant reduction in the need for neurosurgical intervention (OR, 1.00; 95% CI, 0.53–1.90, p = 0.996; I 2 = 59.1%; p = 0.032). CONCLUSION: Current evidence does not support the use of platelet transfusion in patients with tICH on prehospital antiplatelets, highlighting the need for a prospective evaluation of this practice. LEVEL OF EVIDENCE: Systematic Reviews and Meta-Analyses, Level III. Abstract : Supplemental digital content is available in the text.